Genealogi Keilmuan Muḥammad b. ‘Abd al-Wahhāb - Muhammad Chabibi (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2017)
Wahhabism is an Islamic ideological school attributed to a Muslim scholar named Muḥammad b. ‘Abd al-Wahhāb of Najd. ‘Abd al-Wahhāb has carried out religious preaching to promulgate his ideas into a number of regions within the Arabic Peninsula, aiming at also spreading them throughout the world. In doing so, he has been supported by political and military power provided by an Amīr named Muḥammad b. Sa‘ud. ‘Abd al-Wahhāb’s da‘wah sought to invite Muslims to purify their faith and promote Islamic revivalism (Islamic orthodoxy). Employing Michel Foucault’s “theory of genealogy”, this article attempts to look at the relational bond of knowledge and power. The historical analysis finds genealogy within ‘Abd al-Wahhab’s knowledge along with the earlier network of Ḥanbalī’s authorities in Damascus through the ijāzah he accepted from his teachers. Ijāzah is a symbol of the legitimacy of enthusiasm in Islamic scientific genealogy. The associations between religion and politics have been another important factor in the success of the Wahhabi movement.